2016
DOI: 10.1136/bcr-2016-216554
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral osteoma in an unusual location on the mandible

Abstract: Osteoma is a benign, slow-growing, painless, discrete lesion which is characterised with the proliferation of a compact or cancellous bone. Osteomas are rare on the jaws. Lesions of the mandible developed most often in the condyle, angle and margin. Osteoma developed on the genial tubercle area had only been reported in one case. A 50-year-old female patient has been admitted to our department with the symptom of a hard mass under the chin area. In extra-oral and radiographic examinations, a 1×1 cm size, round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Usage of the most effective imaging modality pose a crucial role in the conservative management of the osteomas. Different imaging modalities like occlusal and panoramic radiographs, Waters view, computerized tomography (CT), magnetic resonance imaging (MRI), or CBCT can be used for the radiographic examination of POs (28). It is reported that POs in the craniofacial region are best visualized and localized by means of CT (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usage of the most effective imaging modality pose a crucial role in the conservative management of the osteomas. Different imaging modalities like occlusal and panoramic radiographs, Waters view, computerized tomography (CT), magnetic resonance imaging (MRI), or CBCT can be used for the radiographic examination of POs (28). It is reported that POs in the craniofacial region are best visualized and localized by means of CT (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of osteomas include exostoses, osteochondroma, osteoid osteoma, periosteal osteoblastoma, parosteal osteosarcoma, peripheral ossifying fibroma, Paget's disease, fibrous dysplasia, and odontoma. Careful evaluation of the clinical behaviors, radiographic and histologic features of the lesions are required to reach correct diagnosis (28). Treatment of asymptomatic osteomas is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…2 A combination of trauma and subsequent muscle traction may play a role in the development of osteomas as trauma causes subperiosteal bleeding that locally elevates the periosteum. 4 The continuous muscle traction accentuates the osteogenic reaction stimulated by local bleeding. 6 Although the patient in this case had a history of direct trauma prior to development of the lesion, this theory of combination of local bleeding and muscle traction does not seem to be true for this case as this is an endosteal osteoma and only the development of periosteal osteoma can be influenced by muscle traction.…”
Section: Etiologymentioning
confidence: 99%
“…1,2 It is more frequent in adolescents and young adults with 50% of patients being aged between 10 and 20 years and it predominates in male, with a reported male-to-female ratio of 4:1. 4 The age range for presentation of this lesion is very wide with the average age of diagnosis as 50 years. 1 Among the jaws, mandible is more commonly affected than maxilla with angle and condyle being the most common site followed by the body (molar region) and ascending ramus.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the literature, we noticed variance on the matter of gender predilection. Most authors affirm that there is equal incidence among men and women [ 6 , 7 ], while some claim to have found higher prevalence in men, up to a 2:1 ratio [ 4 , 8 , 9 ], and others in women, with results varying from a 2:1 to 1.5:1 ratio [ 3 , 10 , 11 ]. It has been claimed, even, that the real prevalence of osteomas is unknown [ 12 ], due to most lesions being asymptomatic and never reaching clinical proportions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%